1997
DOI: 10.1042/bj3280193
|View full text |Cite
|
Sign up to set email alerts
|

Identification of essential histidine residues in UDP-N-acetyl-D-galactosamine:polypeptide N-acetylgalactosaminyltransferase-T1

Abstract: UDP-N-acetyl-d-galactosamine:polypeptide N-acetylgalactosaminyltransferases (ppGaNTases) catalyse the initial step of mucin-type O-glycosylation. The activity of bovine ppGaNTase-T1 isoenzyme was inhibited by diethyl pyrocarbonate (DEPC) modification. Activity was partially restored by hydroxylamine treatment, indicating that one of the reactive residues was a histidine. The transferase was protected against DEPC inactivation when UDP-GalNAc and EPO-G, a peptide pseudo-substrate PPDAAGAAPLR, were simultaneousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…Previously, we had reported that a H125A mutation inactivates recombinant bovine ppGaNTase-T1 (24). With a larger data set of ppGaNTases, it is now clear that this position, albeit highly conserved (found in 10 out of 14 ppGaNTase isoforms), is not invariant.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, we had reported that a H125A mutation inactivates recombinant bovine ppGaNTase-T1 (24). With a larger data set of ppGaNTases, it is now clear that this position, albeit highly conserved (found in 10 out of 14 ppGaNTase isoforms), is not invariant.…”
Section: Resultsmentioning
confidence: 99%
“…The second conserved residue in this motif (H211 for ppGaNTases-T1 and aspartate for most other GT1 family members) is also critical for function. We have previously mutated H211 in bovine ppGaNTase-T1 and demonstrated that a H211A mutant is inactive (24). A common theme among DXD motif-containing proteins is their ability to bind nucleoside diphosphate sugars and coordinate manganese ions (7).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This result points out the limitation of using a restricted set of conserved sequences to identify new isoforms; the clones recovered by such methods may be biased against the population of transferases lacking these blocks. When taken together with the results of a site-directed mutagenesis study demonstrating that the histidine residue in this sequence is non-essential (25), it further suggests that this conserved block per se may not play a significant functional role in the transferase activity of these enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…32) In addition, it has several Cys residues conserved in the family, most of which are likely involved in forming disulfide bonds necessary for the proper folding of the enzymes. Two Cys residues among them, which are located at the C-terminus of the DXH motif, are also present in this isozyme.…”
Section: Resultsmentioning
confidence: 99%